Evaluation of the effect of metformin treatment on markers of bone formation and resorption in patients newly diagnosed with Type 2 diabetes - Zuhal Karaca Karagoz; Ibrahim Sahin; Feyzi Kurt; Burcu Ozgur Cil (Medicine Science, 2022)
Type 2 Diabetes Mellitus can affect bone metabolism by many mechanisms and increase the risk of osteoporosis. It has been reported that glucose-lowering treatments, including metformin also have an effect on bone turnover. The aim of this study is to evaluate the effect of metformin treatment on bone formation and resorption in patients with newly diagnosed type 2 Diabetes Mellitus. There were 37 patients in the study population who were newly diagnosed with type 2 Diabetes Mellitus. Fasting plasma glucose level and postprandial plasma glucose level as well as plasma Hemoglobin A1C, calcium, phosphorus, parathyroid hormone, osteocalcin and C-Telopeptide levels were measured before initiation of metformin treatment. The tests were repeated 3 months after the treatment. The levels of fasting plasma glucose and postprandial plasma glucose decreased after 3 months of metformin treatment as expected and the difference was statistically significant. However there was no significant change incalcium, phosphorus and parathyroid hormone levels. There was also a sig-nificant decrease due to Metformin treatment in osteocalcin levels, which is a bone formation mar-ker. Metformin treatment has decreased C-Telopeptide levels as well which is also a bone formation marker. Our results have shown that 3 months of metformin treatment may suppress the bone turno-ver. Another important finding of our study was the reduction in levels of bone formation markers in female patients. Controlledlong-term studies are needed to be conducted in order to manifest the clinical implications of these findings. [Med-Science 2022; 11(4.000): 1715-9]